Zmiany w systemie ocen pracowniczych jako czynnik wzrostu sprawności zarządzania zasobami ludzkimi w PGNiG SA, Regionalnym Oddziale Przesyłu we Wrocławiu - Hnatio, Krzysztof (Changes in the employee evaluation system as a factor increasing the efficiency of HR management in polish oil and gas company - regional transmission division in Wrocław, 2005)
The following report presents a practical example of the evolution in the implemented Employee Evaluation System in Polish Oil and Gas Company Regional Transmission Division in Wroclaw as an instrument increasing the efficiency of HR Management in the company.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1092, s. 580-586